AN ANALYTIC STUDY OF INSTITUTIONAL DEVELOPMENT MODEL OF SHALLOT AGRIBUSINESS FARMERS IN RUMBIA DISTRICT, JENEPONTO REGENCY - Asriadi, Andi Amran; Husain, Nailah; Hasriani (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The objectives of this study were to identify the various types of farmer agribusiness institutions and to investigate the factors that influenced shallot farmers' group institutional growth in Rumbia District, Jeneponto Regency. Simple random sampling was defined as a sampling technique of every item in the population. The study was conducted out by utilizing a field interview technique with onion commodity questionnaires from farmers, collectors, suppliers, and merchants. The study's findings demonstrated that the diversity of marketing forums used by farmers participating in distribution had two channels: first (producers, collectors, traders, consumers) and second (producers, collectors, traders and consumers) (producers, collectors, inter-district wholesalers, district traders and consumers). The farmer group (X1) had a very significant effect on the growth of farmer institutions as a farmer's economic institution using a significant effect coefficient of 0.331 (p 0.001), then the beta coefficient was significant and the direction was positive. This a coefficient was influence of 0.205 (p>0.005), so that the association of farmer groups (X2) had no effect.